FACTORS OF DIVERGENCE BETWEEN PERIPHERAL AND CENTRAL SUBREGIONS: THE CASE OF MAZOVIA PROVINCE, POLAND - Zaborowski, Tomasz (Quaestiones Geographicae, 2020)
The focus of this article is the study of centre–periphery intraregional development disparities using Poland’s largest and most diversified Mazovia Province (Mazowieckie Voivodeship) as an example. The economic downfall of the Radom subregion, in comparison with the booming Warsaw agglomeration, clearly illustrates the polarisation of this province. A research question was if the location of the Radom subregion in Mazovia Province is a significant factor of its relative regression. In order to answer this question, selected development indicators of Mazovian subregions have been compared with their counterparts from surrounding provinces. Research results have shown that a subregion’s location in a big and diversified province is a significant factor of intraregional centre-periphery development discrepancies.